A Medical Decisions Support System in Diagnosis of the Jejunum and Ileum Neoplastic Diseases (Tumors) Based on Video Capsule Endoscopy. - BUDYKINA, Anna; RAUZINA, Svetlana; ZARUBINA, Tatiana; SELEZNEV, Denis; FEDOROV, Evgeniy; IVANOVA, Ekaterina (Studies in Health Technology & Informatics, 2018)
Search of tumors in video capsule endoscopy (VCE) record in some cases presents significant difficulties even for experienced specialist. We made an attempt to develop rules supporting clinical decision for processing of VCE images. An algorithm for assessment of neoplastic diseases of the jejunum and ileum on the basis of VCE to support tactical decision-making of doctors was conducted. The algorithm was implemented as a software module "The conclusion in a capsule" with integrated development environment Visual Studio and the programming language C#.